2008
DOI: 10.1007/s10151-008-0388-0
|View full text |Cite
|
Sign up to set email alerts
|

Colonic carcinoma presenting as strangulated inguinal hernia: report of two cases and review of the literature

Abstract: Inguinal hernia and colonic carcinoma are common surgical conditions, yet carcinoma of the colon occurring within an inguinal hernia sac is rare. Of 25 reported cases, only one was a perforated sigmoid colon carcinoma in an inguinal hernia. We report two cases of sigmoid colon carcinoma, one of which had locally perforated. Each presented within a strangulated inguinal hernia. Oncologically correct surgery in these patients presents a technical challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 18 publications
0
24
0
1
Order By: Relevance
“…Inguinal hernias are a common surgical presentation in the elderly population with a prevalence of 6% 1. This case highlights several issues relating to emergency management of inguinal hernias in older patients.…”
Section: Discussionmentioning
confidence: 88%
“…Inguinal hernias are a common surgical presentation in the elderly population with a prevalence of 6% 1. This case highlights several issues relating to emergency management of inguinal hernias in older patients.…”
Section: Discussionmentioning
confidence: 88%
“…Colon cancer is the most common neoplasm found within any hernia,6 and despite the prevalence of inguinal hernias in the elderly population being approximately 6%,6 dual presentations remain rare. As such, there is no agreed-upon approach to dealing with this condition, with a variety of laparoscopic and open techniques having been trialled 1 3–5…”
Section: Discussionmentioning
confidence: 99%
“…Two previous literature reviews [3,4] revealed that the sigmoid colon was involved in most cases and all patients were male. Out of 28 patients reported, only four had a cecal tumor, presenting in all cases as a right long-standing inguinal hernia that become painful or incarcerated.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of the reported cases, a laparotomic resection of the colon followed a traditional inguinal repair through two separate incisions [2,4]. In cases of perforation or occlusion, most authors performed a colonic resection through the inguinal incision to prevent the peritoneal cavity from contamination and completed the operation via a midline laparotomy [3,5]. Other authors described a transverse left iliac fossa incision for a sigmoid cancer incarcerated into a left inguinal hernia [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation